Restoration of tumour-growth suppression in vivo via systemic nanoparticle-mediated delivery of PTEN mRNA. (November 2018) - Islam, Mohammad; Xu, Yingjie; Tao, Wei; Ubellacker, Jessalyn; Lim, Michael; Aum, Daniel; Lee, Gha; Zhou, Kun; Zope, Harshal; Yu, Mikyung; Cao, Wuji; Oswald, James; et al.
Abstract Phosphatase and tensin homologue deleted on chromosome 10 (PTEN ) is a well-characterized tumour-suppressor gene that is lost or mutated in about half of metastatic castration-resistant prostate cancers and in many other human cancers. The restoration of functional PTEN as a treatment for prostate cancer has, however, proven difficult. Here, we show thatPTEN messenger RNA (mRNA) can be reintroduced into PTEN-null prostate cancer cells in vitro and in vivo via its encapsulation in polymer–lipid hybrid nanoparticles coated with a polyethylene glycol shell. The nanoparticles are stable in serum, elicit low toxicity and enable highPTEN mRNA transfection in prostate cancer cells. Moreover, significant inhibition of tumour growth is achieved when delivered systemically in multiple mouse models of prostate cancer. We also show that the restoration of PTEN function in PTEN-null prostate cancer cells inhibits the phosphatidylinositol 3-kinase (PI3K)–AKT pathway and enhances apoptosis. Our findings provide proof-of-principle evidence of the restoration of mRNA-based tumour suppression in vivo. The reintroduction ofPTEN mRNA into PTEN-null prostate cancer cells via encapsulation in polymer–lipid nanoparticles delivered systemically leads to significant inhibition of tumour growth in mouse models of prostate cancer.